JOB READINESS OF ACCOUNTING STUDENTS IN THE SOCIETY 5.0 ERA WITH THE APPLICATION OF PROFESSIONAL SKILLS ACCORDING TO IASB STANDARDS: A CASE STUDY OF ACCOUNTING STUDENTS UNTAG SURABAYA - Hermawan, Arfindo; Hwihanus, Hwihanus (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to assess the readiness of accounting study programme students in facing the world of work in the Society 5.0 era by applying the professional skills of an accountant according to the International Accounting Standards Board (IASB) standards contained in the International Education Standard (IES) 3. This type of research uses a qualitative approach. data collection techniques were carried out by conducting interviews, observations, and surveys of 10 Accounting students at the University of 17 August 1945 Surabaya. data analysis was carried out by data reduction, data presentation, and conclusion drawing. the results show that accounting students at the University of 17 August 1945 Surabaya have a fairly good readiness in facing the world of work in the digital era. They have a good understanding of technology in accounting, and demonstrate intellectual, interpersonal, personal, and organisational skills that support them in adapting to the professional environment. But there are still some aspects that need to be improved, such as practical experience in the world of work, assertiveness in professional communication, and readiness to face more complex business challenges. With more training and hands-on experience in the world of work, these students have great potential to become competent accountants who are ready to face the challenges of the Society 5.0 era